Moving Home Learning Program (MHLP) as an Adaptive Learning Strategy in Emergency Remote Teaching during the Covid-19 Pandemic - Ardiyansyah, Arief; Setiawan, Eko; Budiya, Bahroin (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
The Covid-19 pandemic had a dangerous impact on early-childhood education, lost learning in almost all aspects of child development. The house-to-house learning, with the name Moving Home Learning Program (MHLP), is an attractive offer as an emergency remote teaching solution. This study aims to describe the application of MHLP designed by early-childhood education institutions during the learning process at home. This study used a qualitative approach with data collection using interviews, observation, and documentation. The respondents involved in the interview were a kindergarten principal and four teachers. The research data were analyzed using the data content analysis. The Findings show that the MHLP has proven to be sufficiently in line with the learning needs of early childhood during the Covid-19 pandemic. Although, the application of the MHLP learning model has limitations such as the distance from the house that is far away, the number of meetings that are only once a week, the number of food and toy sellers passing by, disturbing children's concentration, and the risk of damage to goods at home. The implication of this research can be the basis for evaluating MHLP as an adaptive strategy that requires the attention of related parties, including policy makers, school principals, and teachers for the development of new, more effective online learning models. Keywords: Moving Home Learning Program (MHLP), Children Remote Teaching References:Abdollahi, E., Haworth-Brockman, M., Keynan, Y., Langley, M. J., & Oghadas, S. M. (2020). Simulating the effect of school closure during COVID-19 outbreaks in Ontario , Canada. BMC Medicine, 1–8. https://doi.org/https://doi.org/10.1186/s12916-020-01705-8 Arends, R. I., & Kilcher, A. (2010). Teaching for Student Learning: Becoming an Accomplished Teacher (1st ed.). Routledge. Arysandhi, K. N., & Meitriana, M. A. (2014). Studi Komparatif Motivasi Belajar Siswa pada Mata Pelajaran IPS antara Moving Class dengan Kelas Menetap di SMPN 1 Kerambitan dan SMPN 2 Tabanan Tahun Pelajaran 2013/2014. Ekuitas-Jurnal Pendidikan Ekonomi, 2(1), 30–39. Bawa, P. (2020). Learning in the age of SARS-COV-2 : A quantitative study of learners ’ performance in the age of emergency remote teaching. Computers and Education Open, 1(October), 100016. https://doi.org/10.1016/j.caeo.2020.100016 Bialek, S., Gierke, R., Hughes, M., McNamara, L., Pilishvili, T., & Skoff, T. (2020). Morbidity and mortality weekly report (mmwr) - Coronavirus Disease 2019 in Children — United States, February 12–April 2, 2020. Morbidity and Mortality Weekly Report, 69, 2–6. https://www.cdc.gov/coronavirus/2019-ncov/downloads/pui-form.pdf. Boardman, M. (2003). Changing Times: Changing Challenges for Early Childhood Leaders. Australasian Journal of Early Childhood, 28(2), 20–26. https://doi.org/10.1177/183693910302800205 Bronfenbrenner, U. (1979). The ecology of human development (1st ed.). Harvard University Press. Chen, Y. T. (2020). An investigation of young children’s science and aesthetic learning through a science aesthetic thematic curriculum: A mixed-methods study. Australasian Journal of Early Childhood, 45(2), 127–141. https://doi.org/10.1177/1836939120918503 Choi, N., & Jung, H. (2020). Temperament and Home Environment Characteristics as Predictors of Young Children ’ s Learning Motivation. Early Childhood Education Journal, 1994. https://doi.org/10.1007/s10643-020-01019-7 Counselman, K. P., & Jones, E. (2001). Distance learning in early childhood teacher education: The experience of Pacific Oaks College. Journal of Early Childhood Teacher Education, 22(4), 225–230. https://doi.org/10.1080/1090102010220402 Daniel, S. J. (2020). Education and the COVID-19 pandemic. PROSPECTS, 6. https://doi.org/10.1007/s11125-020-09464-3 Dick, W., Carey, L., & Carey, J. O. (2015). The Systematic Design of Instruction (8th ed.). Pearson. Diningrat, S. W. M., Nindya, M. A., & Salwa. (2020). Cakrawala Pendidikan ,. Cakrawala Pendidikan, 39(3), 705–719. https://doi.org/10.21831/cp.v39i3.32304 Dong, C., Cao, S., & Li, H. (2020). Young children’s online learning during COVID-19 pandemic: Chinese parents’ beliefs and attitudes. Children and Youth Services Review, 118(June), 105440. https://doi.org/10.1016/j.childyouth.2020.105440 Dong, Y., Dong, Y., Mo, X., Hu, Y., Qi, X., Jiang, F., Jiang, Z., Jiang, Z., Tong, S., Tong, S., & Tong, S. (2020). Epidemiology of COVID-19 among children in China. Pediatrics, 145(6). https://doi.org/10.1542/peds.2020-0702 Eliza, D. (2013). Penerapan Model Pembelajaran Kontekstual Learning (CTL) Berbasis Centra di Taman Kanak-Kanak. Pedagogi: Jurnal Ilmiah Ilmu Pendidikan, XIII(2), 93–106. Fadlilah, azizah nurul. (2021). Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini Strategi Menghidupkan Motivasi Belajar Anak Usia Dini Selama Pandemi COVID-19 melalui Publikasi Abstrak. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 373–384. https://doi.org/10.31004/obsesi.v5i1.548 Fenech, M. (2013). Quality early childhood education for my child or for all children?: Parents as activists for equitable, high-quality early childhood education in Australia. Australian Journal of Early Childhood, 38(4), 92–98. https://doi.org/10.1177/183693911303800413 Gibson, M. (2013). “I want to educate school-age children”: Producing early childhood teacher professional identities. Contemporary Issues in Early Childhood, 14(2), 127–137. https://doi.org/10.2304/ciec.2013.14.2.127 Hamzah, N. (2016). Pelaksanaan Pembelajaran BCCT Bagi Anak Usia Dini ; Study Pelaksanaan BCCT Di Tk Islam Mujahidin Pontianak. At-Turats: Jurnal Pemikiran Pendidikan Islama, 10(2), 119–131. Hasan, M. S., & Saputri, D. E. (2020). Pembelajaran PAI Berbasis Moving Class di SMP Negeri 1 Gudo Jombang. Attaqwa: Jurnal Ilmu Pendidikan Islam, 16(September), 113–125. Hew, K. F., Jia, C., Gonda, D. E., & Bai, S. (2020). Transitioning to the “new normal” of learning in unpredictable times: pedagogical practices and learning performance in fully online flipped classrooms. International Journal of Educational Technology in Higher Education, 17(1). https://doi.org/10.1186/s41239-020-00234-x Hodges, C. B., Moore, S., Lockee, B., Trust, T., & Bond, A. (2020). The Difference Between Emergency Remote Teaching and Online Learning. Educase Review. Hussein, E., Daoud, S., Alrabaiah, H., & Badawi, R. (2020). Children and Youth Services Review Exploring undergraduate students ’ attitudes towards emergency online learning during COVID-19 : A case from the UAE. Children and Youth Services Review, 1–7. https://doi.org/10.1016/j.childyouth.2020.105699 Işıkoğlu, N., Ero, A., Atan, A., & Aytekin, S. (2021). A qualitative case study about overuse of digital play at home. Current Psychology. https://doi.org/https://doi.org/10.1007/s12144-021-01442-y A Kilgallon, P., Maloney, C., & Lock, G. (2008). Early childhood teachers coping with educational change. Australian Journal of Early Childhood, 33(1), 23–29. https://doi.org/10.1177/183693910803300105 Kim, J. (2020). Learning and Teaching Online During Covid ‑ 19 : Experiences of Student Teachers in an Early Childhood Education Practicum. International Journal of Early Childhood, 52(2), 145–158. https://doi.org/10.1007/s13158-020-00272-6 Kurniati, E., Kusumanita, D., Alfaeni, N., & Andriani, F. (2021). Analisis Peran Orang Tua dalam Mendampingi Anak di Masa Abstrak. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 241–256. https://doi.org/10.31004/obsesi.v5i1.541 Lopes, H., & Mckay, V. (2020). pandemics : The COVID ‑ 19 experience. International Review of Education, 0123456789. https://doi.org/10.1007/s11159-020-09843-0 Macartney, K., Quinn, H. E., Pillsbury, A. J., Koirala, A., Deng, L., Winkler, N., Katelaris, A. L., & Sullivan, M. V. N. O. (2020). Articles Transmission of SARS-CoV-2 in Australian educational settings : a prospective cohort study. Lancet Child Adolesc Health 2020, 4642(20), 1–10. https://doi.org/10.1016/S2352-4642(20)30251-0 Marina, Indrawati, H., & Suarman. (2019). Application of Moving Class Learning Models and Teacher Pedagogical Competence on Learning Motivation and Student Learning Discipline. Journal of Educational Sciences, 3(1), 72–83. https://doi.org/doi.org/10.31258/jes.3.1.p.72-83 McLean, K., Edwards, S., & Mantilla, A. (2020). A review of community playgroup participation. Australasian Journal of Early Childhood, 45(2), 155–169. https://doi.org/10.1177/1836939120918484 Muhdi, Nurkolis, & Yuliejantiningsih, Y. (2020). The Implementation of Online Learning in Early Childhood Education During the Covid-19 Pandemic. Jurnal Pendidikan Usia Dini, 14(2), 248–261. https://doi.org/https://doi.org/10.21009/JPUD.142.04 Panovska-griffiths, J., Kerr, C. C., Stuart, R. M., Mistry, D., Klein, D. J., Viner, R. M., & Bonell, C. (2020). Articles Determining the optimal strategy for reopening schools , the impact of test and trace interventions , and the risk of occurrence of a second COVID-19 epidemic wave in the UK : a modelling study. The Lancet Child and Adolescent Health, 4642(20), 1–11. https://doi.org/10.1016/S2352-4642(20)30250-9 Piquero, A. R., Riddell, J. R., Bishopp, S. A., Narvey, C., Reid, J. A., & Piquero, N. L. (2020). Staying Home , Staying Safe ? A Short-Term Analysis of COVID-19 on Dallas Domestic Violence. American Journal of Criminal Justice, 601–635. https://doi.org/https://doi.org/10.1007/s12103-020-09531-7 Pramling, I., Judith, S., Elin, T. W., & Ødegaard, E. (2020). The Coronavirus Pandemic and Lessons Learned in Preschools in Norway , Sweden and the United States : OMEP Policy Forum. International Journal of Early Childhood, 0123456789. https://doi.org/10.1007/s13158-020-00267-3 Pribadi, H., & Harjati, P. (2013). Analisis Pembelajaran Fisika dalam Sistem Moving Class di SMP Negeri 1 Pekalongan Lampung Timur Tahun Pelajaran 2012/2013. JPF, 32–41. Project Tommorow & Blackboard. (2017). Trends in Digital Learning: Building teachers’ capacity and competency to create new learning experiences for students. https://tomorrow.org/speakup/speak-up-2016-trends-digital-learning-june-2017.html Rahiem, M. D. H. (2020). The Emergency Remote Learning Experience of University Students in Indonesia amidst the COVID-19 Crisis. International Journal of Learning, Teaching and Educational Research, 19(6), 1–26. http://orcid.org/0000-0002-5618-2486%0AAbstract. Ramdhani, M. T. (2016). Model Pelaksanaan Pembelajaran Pendidikan Agama Islam dengan Sistem Moving Class dalam Meningkatkan Motivasi dan Prestasi Belajar Siswa SMP IT Sahabat Alam. Anterior Jurnal, 15(2), 212–221. Reigeluth, C. M., Beatty, B. J., & Myers, R. D. (2017). Instructional-Design Theories and Models (R. D. Myers (Ed.); IV). Routledge. Sangsawang, T. (2020). Indonesian Journal of Science & Technology An Instructional Design for Online Learning in Vocational Education according to a Self-Regulated Learning Framework for Problem Solving during the CoViD-19 Crisis. 5. Schmerse, D., Anders, Y., Wieduwilt, N., & Tietze, W. (2018). Differential effects of home and preschool learning environments on early language development. British Educational Research Journal, 44(2), 338–357. https://doi.org/10.1002/berj.3332 Schreier, M. (2013). Qualitative Content Analysis (First Edit). SAGE Publications. Shisley, S. (2020). Emergency Remote Learning Compared to Online Learning. Learning Solution. https://learningsolutionsmag.com/articles/emergency-remote-learning-compared-to-online-learning Son, S., & Morrison, F. J. (2010). The Nature and Impact of Changes in Home Learning Environment on Development of Language and Academic Skills in Preschool Children. 46(5), 1103–1118. https://doi.org/10.1037/a0020065 Stephen, C., Ellis, J., & Martlew, J. (2010). Taking active learning into the primary school: A matter of new practices? International Journal of Early Years Education, 18(4), 315–329. https://doi.org/10.1080/09669760.2010.531916 Sudrajat, C. J., Agustin, M., Kurniati, L., & Karsa, D. (2021). Strategi Kepala TK dalam Meningkatkan Mutu Pendidikan pada Masa Pandemi Covid 19 Abstrak. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 508–520. https://doi.org/10.31004/obsesi.v5i1.582 Sumindar, A., & Wahyu, L. (2012). Model Pembelajaran Moving Class Mata Pelajaran Seni Budaya dan Implikasinya terhadap Kemandirian Siswa (Kajian Kasus) di SMA Karangturi Semarang. Catharsis: Journal of Arts Education, 1(2), 21. Supriatna, R., Hafidhuddin, D., & Syafri, U. A. (2018). Model Pembelajaran Beyond Center and Circle Time (BCCT) Berbasis Q.S Lukman Ayat 12-19. Tawazun: Jurnal Pendidikan Islam, 11(2), 1–11. Syarah, E. S. (2020). Understanding Teacher ’ s Perspectives in Media Literacy Education as an Empowerment Instrument of Blended Learning in Early Childhood Classroom. Jurnal Pendidikan Usia Dini, 14(2), 202–214. https://doi.org/https://doi.org/10.21009/JPUD.142.01 Tang, Y., & Hew, K. F. (2020). Does mobile instant messaging facilitate social presence in online communication? A two-stage study of higher education students. International Journal of Educational Technology in Higher Education, 17(1). https://doi.org/10.1186/s41239-020-00188-0 Thompson, M. (2019). Early Childhood Pedagogy in a Socio ‑ cultural Medley in Ghana : Case Studies in Kindergarten. International Journal of Early Childhood, 51(2), 177–192. https://doi.org/10.1007/s13158-019-00242-7 Togher, M., & Fenech, M. (2020). Ongoing quality improvement in the context of the National Quality Framework: Exploring the perspectives of educators in ‘Working Towards’ services. Australasian Journal of Early Childhood, 45(3), 241–253. https://doi.org/10.1177/1836939120936003 UNESCO. (2020). UNESCO’s support: Educational response to COVID-19. Unesco. https://en.unesco.org/covid19/educationresponse/support Vygotsky, L. S. (1978). Mind in Society: The Development of Higher Psychological Processes. Harvard University Press. Wiresti, R. D. (2021). Analisis Dampak Work From Home pada Anak Usia Dini di Masa Pandemi Covid-19. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 641–653. https://doi.org/10.31004/obsesi.v5i1.563 Wiwatowski, M., Page, J., & Young, S. (2020). Examining early childhood teachers’ attitudes and responses to superhero play. Australasian Journal of Early Childhood, 45(2), 170–182. https://doi.org/10.1177/1836939120918486 Yin, R. K. (2018). Case Study Research and Applications Design and Methods (Eliza Wells (Ed.); Sixth Edit). SAGE Publications. Yoshikawa, H., Wuermli, A. J., Britto, P. R., Dreyer, B., Leckman, J. F., Lye, S. J., Ponguta, L. A., Richter, L. M., & Stein, A. (2020). Effects of the Global Coronavirus Disease-2019 Pandemic on Early Childhood Development: Short- and Long-Term Risks and Mitigating Program and Policy Actions. The Journal of Pediatrics, 223(1), 188–193. https://doi.org/10.1016/j.jpeds.2020.05.020 Zhu, X., & Liu, J. (2020). Education in and After Covid-19 : Immediate Responses and Long-Term Visions. Postdigital Science and Education. https://doi.org/https://doi.org/10.1007/s42438-020-00126-3